OBSTACLE OF LEARNING READING IN SECOND-GRADE ELEMENTARY SCHOOL STUDENTS - Cantika, Trie; Arvan Junaidi, Ilham; Ratih Ayu, Imelda (Universitas Negeri Surabaya, 2024)
The beginning reading poses challenges for second-grade elementary school students, impacting their learning outcomes. This research aims to identify the factors hindering the beginning reading ability of second-grade elementary school students. The research method used is qualitative with a case study approach, and data sources include observation, interviews, and documentation. Data analysis techniques involve data reduction, data presentation, and conclusion drawing. The research subjects are second-grade students of SD Negeri 10 Kandis, South Sumatra. The results reveal that the factors inhibiting the beginning reading ability of second-grade students at SD Negeri 10 Kandis include both internal and external factors. Internal factors comprise students' laziness in reading, lack of motivation, lack of interest, lack of attention during learning, low memory retention making it difficult to remember letters, and lack of focus in reading. External factors include family and school-related factors. Family-related factors include busy working parents leading to lack of attention, insufficient parental guidance, and limited interaction and communication with the child. School-related factors include the absence of daily literacy activities before starting lessons, lack of reading corners or literacy corners, unappealing and dull teaching approaches and strategies by teachers, and infrequent use of provided media or teaching aids by the school.